A liberdade, assistida, de adolescentes em cumprimento de medida sócioeducativa e seus fatores de proteção: uma análise sob o olhar da Psicologia Sócio-Histórica - Affonso, Claudinei (2007)
In recent years, psychologists have turned their attention to the strengths and skills that individuals draw upon to overcome situations of adversity. This has led to inclusion of the term resilience in the list of positive qualities which enable the individual to endure stressful situations and to overcome them in a satisfactory way. This ability can be identified by pinpointing a number of protective factors which have proved to be significant in engendering resilience. In so doing, it is also possible to develop intervention strategies to offer assistance in the process of overcoming adversity. Young people who are obliged by order of court to attend counselling find themselves in a socially adverse context, in which they are required to behave in an acceptable manner while being offered appropriate opportunities for social reintegration. The various initiatives for young offenders seek to develop intervention strategies which will enable these young people to overcome their predicament, to benefit from the experience and to rebuild their lives. The aim of this study is to pinpoint the protective factors surrounding young people who are receiving counselling under assisted probation orders. This in turn leads to an examination of intervention strategies, the context of such orders and the various actors involved in this area. The methodology used was that of action research, encompassing all those involved in dealing with young offenders. The different points of view were evaluated and questioned, and new strategies developed. The sessions held with young people at the Fundação Criança and in Jardim Esmeralda, an underprivileged community, both in São Bernardo do Campo, provided an opportunity to analyze the content of the discourse, which in turn gave a qualitative insight into the presence of certain protective factors and issues relating to their needs and strengths, as well as the wider context of such probation orders. Applying the Resilience Quotient Test developed by Reivich. K. & Shatté, A. (2002) gave a quantitative measure of the factors of Emotional Regulation, Impulse Control, Self Efficacy, Causal Analysis, Empathy, Optimism and Reaching Out, with significant results which were subsequently analyzed in qualitative terms. This procedure was also implemented on a voluntary basis with educators on the project who were interested in taking part in the test. Their answers and analyses were assessed both quantitatively and qualitatively, and compared with the results obtained from the adolescents. In general, the results show that innovative forms of intervention are possible if the young people in question are given greater credit and more encouragement to participate. New intervention strategies can be developed by helping them to appropriate the historical, social and cultural context in which they live. This process of appropriation can effect a transformation in the subjects, enabling them to take control of their lives